An investigation of brand equity dimensions and customer retention: A perspective of postpaid telecom subscribers in Lagos State, Nigeria - Ladipo Patrick Kunle; A. Ganiyu Rahim; Peace Nkechi (International Journal of Management and Economics, 2020)
This study investigates brand equity dimensions and customer retention of the Nigerian telecommunications industry. Cross-sectional research design was adopted to survey 368 postpaid subscribers. The respondents were selected through multistage sampling techniques. The four dimensions of brand equity (brand awareness, brand association, perceived quality, and brand loyalty) were found to be correlated with one another and with overall brand equity. Similarly, the four dimensions were correlated to and significantly predicted customer retention. The study concluded that improvement of all the four dimensions of brand equity is indispensably vital to customer retention in the mobile telecom industry. The study recommended that telecom operator that is desirous of sustaining high brand notch in the marketplace should intensify their effort to improve on all the four dimensions of brand equity to enhance subscribers' retention. Findings of this study fill important gaps and contribute to the body of literature related to brand equity dimensions and customer retention from customers' perspective.
Keywords: J11; M10; M31; 650; brand awareness; brand association; perceived quality; brand loyalty; customer retention